Database of anthropogenic vegetation of the Urals and adjacent territories - Golovanov, Yaroslav; Abramova, Larisa (BIO web of conferences, 2021)
The main data on the geobotanical database – Database of antropogenic vegetation of Urals and adjacent territories registered in the Global Index of Vegetation-Plot Databases and the European Vegetation Archive are presented. The database includes more than 4,000 complete geobotanical relevés made between 1984 and 2020. The database contains the territories of 3 subjects of the Russian Federation (the Republic of Bashkortostan, Orenburg, Chelyabinsk regions) and 1 - the Republic of Kazakhstan (Aktobe region). For each relevés, a complete list of species with indication of abundance in points on the Braun-Blanquet scale. The main indicators (total cover, average height of the grass, etc.). For most descriptions, GPS coordinates and location are given. The ecological conditions were assessed with use of average values of E. Landolt scale. In the J. Braun-Blanquet classification system, all communities included in the database belong to nine vegetation classes (7 anthropogenic and 2 semi-natural), 75 associations and various types of communities. Geobotanical relevés with the dominance of such aggressive invasive species ( Acer negundo, Ambrosia psylostachya, Echinocystis lobata, Elodea canadensis, Solidago canadensis, Heracleum sosnowskyi, Hordeum jubatum, Xanthium albinum etc.) are also included in the database.